Predictive Value of Headache for Screening of Refractive Errors in the Pediatric Age Group - Rao, Yashwant Kumar; Padhye, Aparna; Midha, Tanu; Gupta, Ambrish; Kumar, Ajay; Mohan, Kriti (Journal of Pediatric Neurology, 2015)
This article aims to study the predictive value of headache for screening of refractive errors in the pediatric age group. This is a cross-sectional study conducted in the outpatient setting of the Department of Ophthalmology of Lala Lajpat Rai Hospital, associated with Ganesh Shanker Vidyarthi Memorial Medical College, Kanpur (India), during a period of 1 year, including 5,398 children in the age group of 5 to 15 years. Data were collected using a predesigned, pretested questionnaire which included demographic data and chief complaints. All the subjects underwent visual acuity and refractive error testing. Visual acuity was conducted using Snellen's chart and Landolt's C chart. Thereafter, refractive testing was done under cycloplegia and corrective spectacles were prescribed to the patient. Data were analyzed using statistical package for social sciences version 16.0. Chi-square test was applied to analyze the discrete variables. Data were also used to calculate the sensitivity, specificity, positive predictive value, and negative predicative value of headache as a screening tool for the predicting refractive errors in children. Twelve percent of the total population attending the ophthalmic outpatient department belonged to the age group of 5 to 15 years. The male:female ratio was 1.3:1. Out of the total, 58.8% of the subjects had refractive errors. Myopia was the most common refractive error (46.4%) followed by astigmatism (31.3%) and then hyperopia (22.3%). Gender difference was significant (p < 0.01) in the myopic patients; there were more males with myopia than females. Visual acuity testing showed that more than 90% of the patients had visual acuity greater than 6/18 and ∼0.6% belonged to the legally blind category (<6/60). Headache was reported in 65.1% of the total patients. It was found that majority of subjects suffered from headache had myopia (45.8%) followed by astigmatism (29.5%) and hyperopia (24.6%). The sensitivity of headache as a predictor of refractive error was 79.2%, specificity was 54.9%, positive predictive value was 71.5%, and negative predicative value was 64.9%. Headache showed good sensitivity for detection of refractive error. We recommend screening of children presenting with headache for assessment of refractive errors.
Keywords: headache; refractive errors; pediatric age group; hyperopia